Analysis of Food Support Capacity in the District of Sumedang - Purbasari, Citra; Kendarto, Dwi (Jurnal Agritechno, 2025)
The research conducted in Sumedang Regency highlights population growth, land use change, and the role of GIS, as well as the need for in-depth research for the development of more precise and effective agricultural policies. The aim of this study is to analyze food carrying capacity in Sumedang Regency in the face of rapid population growth and land use change; and to determine the impact of land use change on the availability of agricultural land and food carrying capacity in Sumedang Regency. Secondary data sources are used in this research. The research method is quantitative descriptive analysis. Limitations of the study include a focus on Sumedang Regency, dependence on available data, analysis of food carrying capacity with an emphasis on land use change, the use of GIS for spatial analysis, and the application of land optimization methods to selected sites. The analysis results indicate a food deficit in Sumedang Regency due to rapid population growth and land use change, requiring strategies to increase agricultural productivity and food availability policies. Land use change, especially conversion to non-agricultural uses, has a significant impact on the availability of agricultural land, resulting in food deficits and dependence on supplies from other areas, emphasizing the need for wise land planning to maintain a balance between agriculture and the environment.